Optimization of Energy Resource Management: Methodological Aspect - Орищин, Т. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The energy complex, combining industrial and organizational structures, forms a system, the purpose of which is to meet the energy needs of society and ensure energy security. According to the general systems theory all phenomena and processes should be considered as a system. Methodology of systems analysis is an effective instrument of its learning, in which the number of internal communications and external factors is counted. The systems approach to understanding processes and phenomena allows us to study them in the unity of the whole and its separate structures up to a point and is the basis for the development of general principles of optimal data management processes.